Penatalaksanaan Fisioterapi Pada Kasus Frozen Shoulder Dekstra E.C Capsulitis Adesiva Dengan Modalitas Infra Red (IR) Dan Terapi Manipulasi Di RS. Aisyiyah Ponorogo - Wagola, Taufiq .M, Agus Widodo, S.Fis., M.Fis (2016)
Background: Frozen Shoulder capsulitis adesiva often called a syndrome characterized by pain, decreased muscle strength, decreased LGS, thus causing a decrease in functional ability due to the occurrence of adhesions to the joint capsule and cartilage caused by inflammation of the joint capsule. Objective: To determine the benefits of using modalities Infra Red (IR) and Manipulation Therapy can reduce pain, increase muscle strength, improve LGS and improve functional ability dekstra shoulder joints. Results: After treatment for 6 times found to be the result of a decrease in pain motion T1: 9 to T6: 6, painful silence T1: 3 to T6: 1, tenderness T1: 4 to T6: 3. Increased LGS T1: S: 300 -00-900 be T6: S: 400-00-1100, T1: F: 700-00-350 into T6: 800-00-450, T1: T: 300-00-350 into T6: T: 400-00 -500, T1: R (F0): 200-00-350 into T6: R (F0): 350-00-400, T1: R (F70): 300-00-350 into T1: R (F70): 350 -00-400. Increased muscle strength flexion T1: 2 to T6: 3, extension T1: 2 to T6: 3, abduction T1: 2 to T6: 3, adduction T1: 2 to T6: 3, internal rotation T1: 2 to 3, external rotation T1 : 2 to T6: 3. Increased functional capabilities T1: 61.25% to T6: 50%. Conclusion: Infrared (IR) and manipulation therapy can reduce pain, increase muscle strength, improve LGS and improve functional ability dekstra shoulder joints.